The travel writer's handbook how to write--and sell--your own travel experiences - Zobel, Louise Purwin 1922-; Butler, Jacqueline Harmon (Surrey Books, 2012)
"A guide to conceiving, writing, and selling travel writing"--Provided by publisher.